Large discs with large cups: a diagnostic challenge in African patients - Soma, Darshana (My University, 2010)
Objectives To determine in a cohort of 69 African patients with large optic discs and large optic cups, that proportion of patients with physiologic cupping (normal eyes) misdiagnosed as glaucomatous. To evaluate the possible relationship between optic disc size and central corneal thickness. Design and method A case series of 69 patients with large discs (vertical disc height measuring 1.8mm) and large cups (vertical cup to disc ratio 0.6) was evaluated to determine what proportion had glaucoma and what proportion was normal. Patients categorized as normal were further evaluated to determine what proportion were previously misdiagnosed and treated for glaucoma. Patients with a suspected diagnosis of glaucoma, normal tension glaucoma or primary open angle glaucoma were recruited from the glaucoma clinic at St John Eye Hospital. Outcome measures included corrected vertical disc height (VDH), vertical cup to disc ratio (CDR), central corneal thickness (CCT), the relationship between VDH and vertical cup height, the relationship between VDH and CCT, adjusted intraocular pressure (A-IOP), retinal nerve fiber layer analysis and visual fields. vii Results Sixty-nine African patients (138 eyes) with large discs and large cups were evaluated. 41 (59%) were females and 28 (41%) were males. The mean age was 56 years. Of the 69 patients, 51 (74%) had physiologic cupping (normal eyes) and 18 (26%) patients were glaucomatous. Of the group of 51 patients with physiologic cupping, there were 9 patients who were previously misdiagnosed with glaucoma and who had received treatment. VDH ranged between 1.9 and 3.2mm (mean ±SD, 2.3±0.26mm). The distribution analysis of VDH measurements noted the largest cluster around 2.3mm. CCT ranged between 454μm and 618μm (mean±SD, 516±37μm). 107 (77.5%) of the 138 eyes had CCT < 544μm. Conclusion Large cup to disc ratio in relation to large disc size can be normal. It can be misdiagnosed as glaucomatous if objective retinal nerve fiber layer analysis is not carried out. In this study, 9 (18%) patients from a group of 51 patients with physiologic cupping were misdiagnosed as glaucomatous. There was no linear correlation between CCT and VDH in this study. Pearson’s correlation coefficient was 0.13. The majority (77.5%) of eyes had thin corneas (CCT < 544μm).
MMed, Ophthalmology,Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: optic discs; optic cups; optic disc size; glaucoma